2015
DOI: 10.5897/ajfs2015.1291
|View full text |Cite
|
Sign up to set email alerts
|

Screening of antibiotics residues in beef consumed in Ouagadougou, Burkina Faso

Abstract: The anarchic use of antibiotics for therapeutic purposes or as a growth factor in Burkina Faso's breeding is the origin of their residues present in consumed meat. These antibiotics residues have health, technological and microbiological consequences. The objective of this first study is to highlight the antibiotic residues in meat consumed in Ouagadougou, Burkina Faso. A survey was carried out to make an inventory of antibiotics used for animal treatment intended for production and the consequences of such us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…High global prevalence (53.92%) of ESBL-PE was seen in isolates from wastewater and salads. This high frequency could be explained by the fact that in Burkina Faso, the use of antibiotics is excessive and not controlled in human and animal health (Samandoulougou et al, 2015). In addition, the remains of the antibiotics used and the faeces are poured into the hospital and domestic evacuation channels (Akiba et al, 2015;Lan et al, 2019) .…”
Section: Distribution Of Multi-drugs Resistantance Enterobacteria and Associated Resistancementioning
confidence: 99%
“…High global prevalence (53.92%) of ESBL-PE was seen in isolates from wastewater and salads. This high frequency could be explained by the fact that in Burkina Faso, the use of antibiotics is excessive and not controlled in human and animal health (Samandoulougou et al, 2015). In addition, the remains of the antibiotics used and the faeces are poured into the hospital and domestic evacuation channels (Akiba et al, 2015;Lan et al, 2019) .…”
Section: Distribution Of Multi-drugs Resistantance Enterobacteria and Associated Resistancementioning
confidence: 99%
“…Higher levels of histamine were detected in different cheeses in Canada by Chang et al, (1985) and in North Serbia by Švarc-Gajic and Stojanovic, (2011). On the contrary, Bunkova et al (2013) reported that biogenic amine levels in a total of 112 cheese and fermented dairy products examined in the Czech Republic. Researchers reported to histamine levels as not detected level to 24.…”
Section: Resultsmentioning
confidence: 95%
“…2 mg/kg in cheese. Rohani et al, (2013) determined that biogenic amines in some cheese samples by HPLC and reported mean levels of histamine in koopeh, lighvan, red salmas as 70.80 mg/kg, 37.59 mg/kg and 105.21 mg/kg, respectively. The cheese should be stored at low temperature after ripening in order to reduce histamine deposition.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation